Antibiotic Prescription in Young Children With Respiratory Syncytial Virus–Associated Respiratory Failure and Associated Outcomes. Issue 2 (February 2019) - Shein, Steven L.; Kong, Michele; McKee, Bryan; O'Riordan, MaryAnn; Toltzis, Philip; Randolph, Adrienne G.
Abstract : Objectives: To describe antibiotic prescribing practices during the first 2 days of mechanical ventilation among previously healthy young children with respiratory syncytial virus–associated lower respiratory tract infection and evaluate associations between the prescription of antibiotics at onset of mechanical ventilation with clinical outcomes. Design: Retrospective cohort study. Setting: Forty-six children's hospitals in the United States. Patients: Children less than 2 years old discharged between 2012 and 2016 with an International Classification of Diseases diagnosis of respiratory syncytial virus–associated lower respiratory tract infection, no identified comorbid conditions, and receipt of mechanical ventilation. Interventions: Antibiotic prescription during the first 2 days of mechanical ventilation. Measurements and Main Results: We compared duration of mechanical ventilation and hospital length of stay between children prescribed antibiotics on both of the first 2 days of mechanical ventilation and children not prescribed antibiotics during the first 2 days of mechanical ventilation. We included 2, 107 PICU children with respiratory syncytial virus–associated lower respiratory tract infection (60% male, median age of 1 mo [interquartile range, 1–4 mo]). The overall proportion of antibiotic prescription on both of the first 2 days of mechanical ventilation was 82%, decreasing over the study period ( p = 0.004) and varying from 36% to 100% across centers. In the bivariate analysis, antibiotic prescription was associated with a shorter duration of mechanical ventilation (6 d [4–9 d] vs 8 d [6–11 d]; p < 0.001) and a shorter hospital length of stay (11 d [8–16 d] vs 13 d [10–18 d]; p < 0.001). After adjustment for center, demographics, and vasoactive medication prescription, antibiotic prescription was associated with a 1.21-day shorter duration of mechanical ventilation and a 2.07-day shorter length of stay. Ultimately, 95% of children were prescribed antibiotics sometime during hospitalization, but timing, duration, and antibiotic choice varied markedly. Conclusions: Although highly variable across centers and decreasing over time, the practice of instituting antibiotics after intubation in young children with respiratory syncytial virus–associated lower respiratory tract infection was associated with a shortened clinical course after adjustment for the limited available covariates. A prudent approach to identify and optimally treat bacterial coinfection is needed. Abstract : Supplemental Digital Content is available in the text.